Edward Conze (tr. y ed.) The Large Sutra on Perfect Wisdom, with the Divisions of the Ahhisamayalankara, Berkeley, University of California Press, 1984, xviii + 697 pp. - Preciado Solís, Benjamín (Estudios de Asia y África, 1989)
-